2005
DOI: 10.1641/0006-3568(2005)055[0360:teotes]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of the Endangered Species Act: A Quantitative Analysis

Abstract: Population trends for 1095 species listed as threatened and endangered under the Endangered Species

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
124
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(134 citation statements)
references
References 21 publications
2
124
1
Order By: Relevance
“…The great majority of threatened freshwater fish in Australia are within the lifespan of their first recovery plan, and it is unrealistic to expect recovery to occur in the relatively short period of recovery action. The US Threatened Species Act (TSA) requires the identification of population trend as an indicator of whether a species is recovering or not (Scott et al 2005;Taylor et al 2005). Under the TSA biennial, reporting of population trend is required, providing insight into whether recovery actions are effective, and/or whether changes are required.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The great majority of threatened freshwater fish in Australia are within the lifespan of their first recovery plan, and it is unrealistic to expect recovery to occur in the relatively short period of recovery action. The US Threatened Species Act (TSA) requires the identification of population trend as an indicator of whether a species is recovering or not (Scott et al 2005;Taylor et al 2005). Under the TSA biennial, reporting of population trend is required, providing insight into whether recovery actions are effective, and/or whether changes are required.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of some specific management actions (e.g. the identification of critical habitat) on recovery trajectory has been scrutinised but the results may be contradictory (Taylor et al 2005;Gibbs and Currie 2012) and the majority of management interventions have not been examined. For freshwater fish, there is a relatively common suite of management activities employed to recover threatened species, including stock enhancement with captive-bred individuals, translocation, habitat rehabilitation, legislative protection, remediation of barriers to fish passage, improved water-quality and flow management, and control of alien species (Cowx 2002;Helfman 2007;Lintermans 2013a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative analysis has shown that the longer a species has been placed on a list of threatened or endangered species, the more likely it is to recover (Taylor et al 2005). Many agencies have taxonomic standards that must be met prior to inclusion in a listing.…”
Section: Listing Species For Protectionmentioning
confidence: 99%
“…While 'whole ecosystem' approaches, such as multispecies recovery plans, are desirable, they can be less effective, due to their broad-based coverage and less explicit linkage between the biology and recovery goals of each species (Boersma et al 2001, Clark and Harvey 2002, Taylor et al 2005, Rahn et al 2006. To be successful, single or multispecies plans must explicitly integrate species biology into the recovery efforts (Tear et al 1995, Boersma et al 2001, Clark and Harvey 2002.…”
Section: Introductionmentioning
confidence: 99%